Bulbophyllum karbianglongensis (Orchidaceae, Epidendroideae), a new species from Assam, India - Gogoi, Khyanjeet; Hondiqui, Rituraj (Lankesteriana: International Journal on Orchidology, 2021)
A new epiphytic Bulbophyllum belonging to section Cirrhopetaloides is described from tropical mixed evergreen forests of Karbi Anglong (Assam, India) with coloured photographs and line drawings. It is allied to the Bulbophyllum bicolor, B. venulosum and B. blaoense, but differs in the size and shape of pseudobulbs, the shape of the leaf blade, and flower size. A detailed description with corresponding color photos and information on the habitat is provided.